Primary school physical education management: Profiles and predictors in Central Java - Adi S; Hilmy Aliriad; Andi Nova; Guntur Firmansyah; Wahyu Arbanisa (Journal Sport Area, 2023)
Effective management allows teachers to see and handle student learning problems. This study aimed to determine the physical education management of elementary school teachers in Central Java and its predictors. This research is quantitative with data description and correlation. Using purposive sampling, the total number of respondents was 50 physical education teachers at the elementary level in Central Java. The data was processed using descriptive statistics, data normality, and correlation. The subjects studied had a minimum teaching experience of 1 year. Data collection techniques include instruments and observation by physical education teachers. The instruments included planning, implementation, and evaluation of physical education management. The questionnaire uses a scale of 1-4. In terms of age and length of teaching, researchers used correlation analysis. Correlation data were processed using SPSS Version 21. The management of physical education in Central Java is in the "good" category. Physical education management includes planning, implementation, and evaluation. Length of teaching and age are not predictors in physical education management. Most physical education teachers are linear and have at least a bachelor's degree. Further studies are needed involving many teachers and other variables to determine predictors. The results of this study contribute consideration, support, and contribution of ideas to stakeholders to improve the quality of physical education. The role of management is crucial in enhancing teachers’ ability to achieve educational goals in general.